Electroluminescence spectra of an STM-tip-induced quantum dot - Croitoru, Mihail D.; Gladilin, Vladimir N.; Devreese, Jozef T.; Kemerink, Martijn; Koenraad, Paulus M.; Sauthoff, K.; Wolter, Joachim H. (Physical review. B, Condensed matter and materials physics, 2004)
We analyze the electroluminescence spectrum of an STM-tip-induced quantum dot in a GaAs surface layer. A flexible model has been developed that combines analytical and numerical methods and describes the key features of many-particle states in the STM-tip-induced quantum dot. The dot is characterized by its depth and lateral width, which are experimentally controlled by the bias and current. We find, in agreement with experiment, that increasing the voltage on the STM tip results in a redshift of the electroluminescence peaks, while the peak positions as a function of electron tunneling current through the STM tip reveal a blueshift.
Gesehen am 09.12.2019